Development of blended learning-based e-learning to improve students' concept understanding in the COVID-19 pandemic era - Ihsan, Muhammad Shohibul; Husain, Pahmi; Fauziah, Nurul; Alyaminy, Ishmah Humaidatul Aminah Zaim (Journal of Research in Instructional, 2024)
Information technology plays a crucial role in online learning, and schools must adapt to the pandemic by utilizing e-learning as a learning medium. This research aims to produce e-learning based on a blended model that is feasible, practical, and effective for increasing students' understanding of concepts. This research uses the ADDIE development model. The product developed consists of a learning implementation plan, e-learning media, and concept understanding test instruments validated by three expert. Data instruments consist of questionnaires assessing feasibility, practicality of learning, and concept understanding test instruments. The validation results show that the average percentage of the feasibility of lesson plans is 88.6% (very feasible), the e-learning media is 85.1% (very feasible), and the concept understanding instruments is 84.6% (very feasible). The practicality test results showed that the student response was 79.3% with practical criteria, the teacher response was 83% with very practical criteria and the implementation of learning was 78.7% with practical criteria. E-learning media is effective in increasing students' conceptual understanding with an average N-gain score of 67 with medium criteria. Based on this description, it can be concluded that e-learning media based on the blended model is very feasible, practical, and effective for increasing students' understanding of concepts in chemistry learning.